CSR (CORPORATE SOCIAL RESPONSIBILITY) MANAGEMENT PROGRAM IN EDUCATIONAL PROGRAM IN KEPULAUAN MERANTI REGENCY OF RIAU PROVINCE: A CASE STUDY IN ENERGI MEGA PERSADA (EMP) MALACCA STRAIT SA - Hafizan, Hafizan Hafizan; Sari, Eliana; Saam, Zulfan (JERAM, 2018)
This study aimed to determine how the planning, organizing, implementing and  monitoring of the CSR (Corporate Social Responsibility) of EMP Malacca Strait SA in the field of education in Kepulauan Meranti Regency of Riau Province, held from June 2016 to September 2016. The research approach used was the qualitative approach (qualitative research). This qualitative research was more specifically directed to the use of the case study method. Data were collected from interviews, observations, study and documents. The data analysis used a method collated by Mathew B. Miles and Michael Huberment, which is called the interactive data analysis models by Burhan Bungin. Data were collected from interviews, observations, study and documents. The analysis consisted of three flows of activities that occurred simultaneously, namely induction, data presentation and conclusion/verification. The results showed that the planning of CSR education program was carried out together with stakeholders at the operation (collaborative), and this ensured that EMP MSSA’s CSR program was an integral part of the purpose or goal of the society at the local site. EMP MSSA organized the program by creating an internal special unit assigned to supervise the program; meanwhile, the special unit was under the control of the Communication Manager, who was assisted by the CSR Coordinator and CSR officer, who have competence and experience in handling CSR program. The CSR program of EMP MSSA was implemented in physical and non-physical forms, such as formal and non-formal education scholarships and education infrastructure assistance. This CSR program was conducted through ongoing assistance by the CSR Officers of EMP MSSA team so that all programs will benefit every year by involving the Community, the Company, and the Regional Government. The outcome of the CSR programs, both physical and non-physical education was directly very supportive of educational activities and the human resources in the District of the Kepulauan Meranti.Keywords: Corporate Social Responsibility (CSR) and education sector